Infographic. Keep it cool and beat the heat: cooling strategies for exercise in hot and humid conditions - Bongers, C. C. W. G.; de Korte, J. Q.; Eijsvogels, T. (British Journal of Sports Medicine, 2021)
Environmental conditions for the upcoming Tokyo Summer Olympics (32th Olympiad) are expected to be extremely challenging for athletes. The high ambient temperature, radiant temperature and absolute humidity, in combination with the urbanisation and heat storage in crowded stadiums, will limit the capability of athletes to dissipate the exercise-induced heat production. Significant elevations of core temperature may occur, leading to an increased risk to develop heat-related disorders and a substantial deterioration of exercise performance. Therefore, application of cooling strategies prior to (precooling) or during exercise (percooling) is highly recommended. In this infographic, we will summarise the latest scientific insights on the effectiveness of cooling strategies.